PENGARUH RETURN ON ASSETS, NET PROFIT MARGIN, DEBT TO EQUITY RATIO, SIZE PADA PERATAAN LABA - Arya Dwiputra, I Made; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2016)
Income smoothing is a deliberate action taken to reduce fluctuations in earnings, where managers wear certain accounting methods to reduce the profit fluktusi. Income s moothing management practices with the aim of reducing the tax debt, increase the confidence of investors, can strengthen the relationship between managers and employees. Factors examined in this study consists of one dependent variable income smoothing and four independent variables, return on assets, netprofit margin, debt to equity ratio and firm size. The study was conducted on banking companies listed in the Indonesia Stock Exchange during the observation period 2010-2013. The samples obtained were 24 enterprises with non-probability sampling methods, particularly purposive sampling. The analysis technique used is the logistic regression analysis. The analysis finds that the return on assets and the size of the company does not affect the income smoothing practices. As well as the net profit margin and debt to equity ratio affect the income smoothing practices.
Keywords: income smoothing, return on assets, net profit margin, debt to equity ratio, the size of the company